Can Smartphones Detect Geomagnetic Storms? - S. F. Odenwald (Space Weather)
Abstract Several smartphone models on the Android and iOS platforms have been investigated for their ability to detect geomagnetic storms. Although this capability could have scientific application, there is a growing commercial interest in using smartphones for precision location applications not involving the GPS system. Under these circumstances, geomagnetic storms could in principle interfere with navigation accuracy. The ability of smartphones to detect geomagnetic disturbances has been tested by developing synthetic magnetometer data for two historical storm events: October 29, 2003 (G5) and July 15, 2012 (G2). These were created by combining typical sensor noise profiles with actual magnetic observatory data, and also by using a Helmholtz coil to calibrate the magnetometer responsivity near 1 microTesla. A comparison of the iPhone 6S, Samsung Note 5, Galaxy S8, and S9 responses based upon their actual ambient noise measurements reveals that for the high and mid‐latitude simulations, storms stronger than G2 (Kp = 6) provided indications of detectability, with the strongest detections occurring for the high‐latitude simulations. The low‐latitude simulated observations near North American latitudes of +38° tended to register storm events at about G4 (Kp = 8) or above. The degree to which geomagnetic storms interfere with precision position measurement applications can be significant at high latitudes for the occasional strong storm events during the peak of the sunspot cycle, but are probably not a significant source of error at other times for most low‐latitude conditions.